Francesco Parona (1842–1908) and his contributions to our understanding of surgery through anatomy. Issue 5 (19th March 2012) - Malenfant, Jason; Walters, Andrew; Kralovic, Sarah; Robitaille, Martin; Schaefer, Jamie; Tubbs, R. Shane; Loukas, Marios
<x xml:space="preserve">Abstract</x> Much of the life of Francesco Parona and many of his contributions to medicine are unknown outside of Europe. Parona made novel contributions to many surgical techniques and medical treatments and was an active member of society and the Italian political regime. Parona's name lives on eponymously by his "space" in the forearm. This paper will discuss the personal life and medical contributions of Francesco Parona. Clin. Anat. 26:547–550, 2013. © 2012 Wiley Periodicals, Inc.